2005
DOI: 10.1101/gad.1365805
|View full text |Cite
|
Sign up to set email alerts
|

Surfing with the tunicates into the post-genome era

Abstract: This year is the centenary of Edward G. Conklin's signal findings in embryology: the elucidation of complete cell lineages and the discovery of localized maternal determinants. Conklin used ascidian embryos to elucidate universal principles in embryology. A century later, ascidians, or sea squirts, have not only entered the postgenome era, but in many ways are leading the way to the promise of a "systems-level" understanding of complex processes such as notochord formation, neurogenesis, and even behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 20 publications
1
34
0
Order By: Relevance
“…It has been suggested that the cupular strand evolved from the cupular organ, and the capsular organ from the first (modified from Mackie and Burighel, 2005). of their gonads, are divided into two orders, Enterogona and Pleurogona (Table 1). With their 3000 species, ascidians are the most frequently studied tunicates, and some species, e.g., the solitary enterogonid Ciona intestinalis, (the genome of which was recently sequenced) and the colonial pleurogonid Botryllus schlosseri, have become reference organisms for developmental and evolutionary studies (Passamaneck and Di Gregorio, 2005;Satoh and Levine, 2005;Manni et al, 2007).…”
Section: Tunicatesmentioning
confidence: 99%
“…It has been suggested that the cupular strand evolved from the cupular organ, and the capsular organ from the first (modified from Mackie and Burighel, 2005). of their gonads, are divided into two orders, Enterogona and Pleurogona (Table 1). With their 3000 species, ascidians are the most frequently studied tunicates, and some species, e.g., the solitary enterogonid Ciona intestinalis, (the genome of which was recently sequenced) and the colonial pleurogonid Botryllus schlosseri, have become reference organisms for developmental and evolutionary studies (Passamaneck and Di Gregorio, 2005;Satoh and Levine, 2005;Manni et al, 2007).…”
Section: Tunicatesmentioning
confidence: 99%
“…In recent years, solitary ascidian species (Ciona intestinalis, Ciona savignyi, Halocynthia roretzi) have emerged as model organisms for studying the molecular control of em-bryogenesis and differentiation of specific cell lines (Nishida, 2002a,b;OdaIshii et al, 2005;Passamaneck and Di Gregorio, 2005;Satoh and Levine, 2005;Dufour et al, 2006), and their genome has been partially or fully sequenced (Dehal et al, 2002;Yokobori et al, 2003). Although less well studied at the molecular level, compound ascidians have the advantage that, in the same organism and at various levels (morphological, biochemical, molecular), several developmental pathways (embryogenesis, blastogenesis, and regeneration) leading to adult, filter-feeding zooids may be compared.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we made use of the extensive available molecular tools in Ciona (Satoh and Levine, 2005) to address the molecular mechanism of the establishment of the anteroposterior difference in the animal hemisphere. We show that there is a global difference between the anterior and posterior ectodermal lineages set up autonomously from the eight-cell stage in the ascidian embryo.…”
Section: Introductionmentioning
confidence: 99%